Attitudes and beliefs of nursing students toward sexual healthcare: A descriptive study. Issue 1 (3rd April 2021) - Güdül Öz, Hatice; Balcı Yangın, Hatice; Ak Sözer, Gülşen
Abstract: Purpose: This study aimed to determine the attitudes and beliefs of the nursing students toward sexual healthcare and the obstacles they encounter. Methods: This descriptive study included 475 nursing students. Findings: The total Sexual Attitude and Belief Survey score was associated with many characteristics such as nursing year, mothers' educational status; talking about sexuality, receiving sexual health education, the status of clinical sexual health evaluation; having difficulty in providing sexual healthcare to the opposite sex, feeling shy about providing sexual healthcare ( p  < 0.05). Practice Implications: The result of this study showed that nursing students have negative beliefs and attitudes toward sexual healthcare.